All of an instant - Garfinkle, Richard (New York : Tor, 1999)
A novel on the discovery of a medium of existence outside of time. It is called the Instant and from it one can influence the past and the future. It is a place of permanent war, as forces vie for this influence, and the novel's hero is one of the warriors.
"A Tom Doherty Associates book."
Keywords: Cosmology -- Fiction; Space and time -- Fiction; Alternative histories; Science fiction